Effects of gender diversity management on perceptions of organizational attractiveness: The role of individual differences in attitudes and beliefs. - Martins, Luis L.; Parsons, Charles K. (Journal of Applied Psychology, 2007)
In this study, the authors examined how individual gender-related attitudes and beliefs affect the reactions of men and women to gender diversity management programs in organizations. They found that whereas there were no significant between-sex differences in the effects of gender diversity management on organizational attractiveness, there were strong within-sex differences based on individual attitudes and beliefs. Specifically, within the sexes, centrality of one's gender identity, attitudes toward affirmative action for women, and the belief that women are discriminated against in the workplace moderated the effects of gender diversity management on organizational attractiveness. The findings, combined with prior research, suggest that it is critical for organizations to incorporate efforts to manage perceptions of gender diversity management programs into their diversity management strategies.